Strategic Insights into Educational Assessment: The Implementation and Constraints of SIMCPM in Monitor-ing Student Outcomes - Seftin Fitri Ana Wati; Fitri, Anindo Saka; Vitianingsih, Anik Vega; Najaf, Abdul Rezha Efrat (Universitas Pembangunan Nasional Veteran Jawa Timur, 2023)
In response to the evolving challenges in educational institutions, the Ministry of Education and Culture emphasizes the crucial role of effective information systems in achieving optimal educational objectives. This study introduces the Student Learning Achievement Information System (SIMCPM) as a strategic solution for systematically monitoring and evaluating student performance. The research explores the implementation of SIMCPM, focusing on its role in functional testing within educational environments. With a user-centric approach, the study investigates how SIMCPM can be integrated as an innovative tool for monitoring student learning achievements, specifically in displaying grade and attendance data. The methodology outlines the comprehensive approach to SIMCPM's development, emphasizing the use of Laravel 8 for back-end infrastructure and HTML, CSS, and JavaScript for UI/UX development. Data visualization development is highlighted, showcasing the integration of ApexCharts.JS for effective communication of educational metrics. Functionality testing ensures the reliability of the system, encompassing testing scenarios, integration testing, load and performance testing, and mobile and tablet functional testing. Results and discussion present the outcomes of SIMCPM's implementation, including data simulation, dashboard rendering, and functionality testing. The study introduces dashboard features for students, lecturers, and the Head of Study Program, emphasizing speed, efficiency, and data visualization quality. Functionality testing results confirm the robustness of the system. The subsequent section interprets the results, addressing implications, strengths, limitations, and potential improvements in the SIMCPM system. The conclusion recommends continuous testing with real-time data, user feedback integration, and potential enhancements such as predictive analytics and personalized learning recommendations to ensure sustained effectiveness in supporting academic processes. Overall, SIMCPM emerges as a promising tool for efficient academic management, subject to continuous refinement and innovation.